Enhanced adsorption property of TiO2 based nanoribbons produced by alkaline hydrothermal process - Ariyanti, Dessy; Mo’ungatonga, Satriani; Gao, Wei (METANA, 2020)
TiO2 is a semiconductor material with endless potential for the development of renewable energy as well as in the environmental field application. With various methods, TiO2 nanostructures with various morphology, properties and application can be developed. In this paper, the synthesis of TiO2 based nanoribbons with high adsorption property produced by alkaline hydrothermal methods were investigated. Its morphology, crystal structure and physical properties were characterized using Scanning Electron Microscope (SEM), X-ray diffraction (XRD), Fourier-transform infrared (FTIR) and Brunauer-Emmett-Teller (BET) surface area analysis. The result shows that by controlling the hydrothermal processing time, different morphology and structures of TiO2 nanoribbons with different adsorption properties can be obtained. The nanoribbons produced via alkaline hydrothermal method has width 200-300 nm and length up to several microns. It also possesses fair adsorption capacity over dyes (Rhodamine B and Methyl orange) considering its large surface area and high pore volume.Â